PETERNAKAN LEBAH KELULUT DI TAHURA SULTAN ADAM MANDIANGIN SEBAGAI SUMBER BELAJAR IPS: Kelulut Beekeeping In Tahura Sultan Adam Mandiangin As An IPS Learning Resource - Rusmaniah, Rusmaniah; Syaharuddin, Syaharuddin; Subiyakto, Bambang (Anterior Jurnal, 2024)
According to the philosophy of constructivism, knowledge is constructed by humans through interaction with their environment. Learning through the environment is one of the effective ways to improve students' understanding, skills, and attitudes. Kelulut beekeeping in Tahura Sultan Adam Mandiangin is one of the environments that can be used as a source of IPS learning. This study aims to determine how kelulut beekeeping in Tahura Sultan Adam Mandiangin can be used as a source of IPS learning. This study uses a qualitative approach with a descriptive method. The data collection techniques used are observation, interview, and documentation. The results of the study showed that beekeeping in Tahura Sultan Adam Mandiangin can be used as a source of IPS learning for class VII of the Merdeka curriculum, especially on the material of environmental diversity and environmental economic potential.